A case report of Kocher Debre Semelaigne syndrome – Congenital hypothyroidism with pseudomuscular hypertrophy - Fatima, Nidha; Adil, Faraaz; G Pathan, Habib (Indian Journal of Child Health, 2023)
Kocher Debre Semealaigne Syndrome (KDSS) is a rare condition with the manifestation of hypothyroidism associated with pseudomuscular hypertrophy. This syndrome is rare in countries with screening programs for hypothyroidism at birth. We are reporting a rare case of KDSS in which earlier diagnosis and treatment would result in the reversal of many symptoms. The main objective of presenting this case is to enlighten pediatricians about prompt diagnosis and timely management to prevent avoidable complications.